(Re)-defining Chitrangada- The Queer Journey from Tagore to Rituparno Ghosh (Global Journal of Human-Social Science, 2024)
The third gender identity, in India, has always been disparaged by the heterosexuals. The survival of "third gender" can be traced in the rudimentary Vedic literatures of India, where, as per prakriti or nature, gender has been clearly divided into pums-prakriti or male, stri-prakriti or female, and tritiya-prakriti or the third sex. The third sex is considered as an intrinsic union of the male and female natures so intensely that they cannot be marked as male or female in the collective sense. The interaction of "gender" and "sex" creates a problem as both are frequently considered the same. The word "sex" denotes biological sex and "gender" as psychological behaviour and identity. The term prakriti or nature conversely implies both facets in concert as one intricately entwined and cohesive unit. Hence the "heterosexual matrix" -an ideal order between sex, gender, and sexuality generated during the modern era (Butler 1990), not only categorized gender borderlines, but promoted the gender order as being implicitly heterosexual.
Keywords: heterosexual matrix; androgynous; identity; liberation